Mapalus Sebagai Model Pendampingan Pastoral Bagi Keluarga Berduka Di Minahasa - Evalien Dina Yuditraida Turangan; Marhaeni Mawuntu; Jacob Terry (PT. Giat Konseling Nusantara, 2025)
This paper explores Mapalus as a model of pastoral care, particularly within the Minahasan community and its approach to supporting grieving families. Mapalus, a traditional system of mutual cooperation, embodies deep values of solidarity, love, collaboration, and communal responsibility. These values resonate with the principles of contextual and participatory pastoral ministry. Pastoral accompaniment in the Mapalus tradition is not limited to physical assistance but extends to emotional and spiritual support through shared presence and collective involvement during times of mourning. The theological reflection in this study highlights the need to develop a pastoral theology rooted in local cultural values as a form of inculturation of the Christian faith into Indonesian social life. Thus, Mapalus offers a relevant and applicable pastoral paradigm for strengthening congregational life and promoting contextual ministry within the church.